2005
DOI: 10.1002/jnr.20447
|View full text |Cite
|
Sign up to set email alerts
|

Non-FK506-binding protein-12 neuroimmunophilin ligands increase neurite elongation and accelerate nerve regeneration

Abstract: Neurotrophic activity of neuroimmunophilin ligands (FK506 and its nonimmunosuppressant derivatives) has been assumed to be mediated by the FK506-binding protein-12 (FKBP-12). We recently showed that activity is retained in hippocampal neurons from FKBP-12 knockout mice, indicating that binding to FKBP-12 is not necessary. Here we show that three nonimmunosuppressant FK506 derivatives (V-13,450, V-13,629, and V-13,670) that do not bind FKBP-12 (>12.5 mM affinity) are equipotent to FKBP-12 ligands (FK506, V-10,3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
37
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 44 publications
0
37
0
1
Order By: Relevance
“…Both studies indicate that binding to FKBP-12 is not required for neurotrophic activity. Similarly, non-immunosuppressant derivatives of FK506 that lack FKBP-12 binding are found to stimulate neurite elongation in SH-SY5Y cells (Gold et al, 2005). It is likely that binding to members of the FKBP family other than FKBP-12 underlies the neurotrophic activity of these agents.…”
Section: Introductionmentioning
confidence: 99%
“…Both studies indicate that binding to FKBP-12 is not required for neurotrophic activity. Similarly, non-immunosuppressant derivatives of FK506 that lack FKBP-12 binding are found to stimulate neurite elongation in SH-SY5Y cells (Gold et al, 2005). It is likely that binding to members of the FKBP family other than FKBP-12 underlies the neurotrophic activity of these agents.…”
Section: Introductionmentioning
confidence: 99%
“…[7] The only other known natural product members of this structure class are meridamycin, from a Venezuelan isolate of Streptomyces hygroscopius, [8] and the antascomicins, from a Chinese soil Micromonospora sp., [9] which also bind to FKBP12 but are not immunosuppressive. Recent literature reports note that FKBP-binding polyketides can exhibit separate and distinct immunosuppressive and neurotrophic pharmacologies, [10] with non-immunosuppressive inhibitors of FKBPs having potential application against important neurological disorders such as multiple sclerosis, [11] traumatic spinal cord injury [12] and Parkinsons disease. [13] In the absence of new natural product members of this structure class, exploration of the pharmacophore defined by FK506 and rapamycin has relied on virtual screening, [14] genetic engineering [15] and precursor-directed biosynthesis, the latter manipulating polyketide synthases (PKS) to incorporate unnatural starter unit carboxylic acids, [16] chain units [17] and terminating pipecolic acid mimics.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequent studies, spanning the last decade, revealed potent neuroprotective and neuroregenerative properties of immunophilin ligands in both culture and animal models [6]. However, the mechanisms underlying these trophic effects are still largely unknown, though the role of FKBP52 has been implicated in a number of studies [7].…”
Section: Introductionmentioning
confidence: 99%